(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In this paper, the author intends to present the application of Unified Power Factor Controllers (UPFC) to control the frequency of three area interdependent and interconnected reheat and hydro systems by controlling the frequency of the system under disturbance due to load variations. Efficacy of the PID controllers to regulate the system dynamics has already been analyzed. By the use of fuzzy logic controllers, the system dynamics is further enhanced and the furtherance in the results is ascertained. This paper also demonstrates the superiority of Fuzzy Logic Controller (FLC) in connection with PID controllers and the UPFC. This paper also discusses the mathematical model of the system.